Evaluation of the effect of selected social and demographic criteria on the frequency of the consumption of lunch and products purchased at school by pupils - Kwiatkowska, Małgorzata; Walczak, Zbigniew; Wawrzyniak, Agata (Journal of Medical Science, 2017)
Introduction. The research shows that eating disorders currently occur in 22% of girls and 28% of boys. Such high overweight and obesity rates are often caused by unbalanced diet, low nutritional awareness of students and parents and, in consequence, bad nutritional habits developed at home. Nutritional awareness of mothers can affect the  dietary behaviour and choices of children and, in consequence, their proper nutritional status. Aim. The aim of the research was to evaluate the frequency of the consumption of breakfast and lunch prepared at home and the frequency of purchases in school shops and vending machines in relation to the child’s sex and the mother’s educational level.Material and Methods. The research material consisted of a survey questionnaire from 76 children aged 9 years, containing questions related to the frequency of consuming breakfast and lunch prepared at home, the frequency of purchasing food products in school shops/vending machines in the past three months and the types of those products.Results. On the basis of conducted research, it was found that the sex of a child did not have any effect on the number of meals consumed (p = 0.14), the frequency of consuming breakfast at home (p = 0.44), the frequency of consuming lunch (brought from home) at school (p = 0.46), or the frequency of purchasing products in school shops/vending machines (p = 0.50). It was found that mothers’ educational level had an effect on dietary habits of children (p
Keywords: students; frequency; breakfast consumption; purchase of products at school; sex; mother’s educational level; nutritional status